Advanced Perioperative Nursing Care and Multidisciplinary Coordination in the Management of Patients With Congenital Heart Disease - Alhazmi, Amal Ayyadah S.; Khloud Mazki Alenazi; Ahmed Ali Ahmed Eshwi; Shaqra Mohammed Mohammed Awaji; Ibrahim Abdullah Al-Zubni; Ahmed Hassan Alrashidi; Rahma Serihan Alharbi; Areej Ali Saleh Shook; Mohammed Hamdan Abdulhadi Alosaimi; Sakinah Naif Alnakhli; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Congenital heart disease (CHD) encompasses diverse structural and functional cardiac anomalies that significantly impact neonatal and pediatric morbidity and mortality. Aim: To explore advanced perioperative nursing care and multidisciplinary coordination in managing CHD patients undergoing surgical interventions. Methods: A comprehensive review of perioperative strategies, including preoperative evaluation, intraoperative monitoring, and postoperative management, was conducted, emphasizing individualized care and team collaboration. Results: Advances in diagnostic imaging, cardiopulmonary bypass, and minimally invasive techniques have improved surgical outcomes. However, success relies on tailored perioperative planning, vigilant monitoring, and effective interdisciplinary communication. Key challenges include hemodynamic instability, airway management, and postoperative complications such as arrhythmias and pulmonary issues. Conclusion: Optimal outcomes in CHD surgery require meticulous nursing care, adaptive strategies, and coordinated teamwork to ensure safety and enhance survival.